A novel protein NFKBIL-1 regulates the activity of key transcription factors - Mankan, Arun Kumar (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2008)
Inflammation is a physiological process initiated in response to an injury or infection. Proper execution of the inflammatory response requires activation of several pro- inflammatory transcription factors. Nuclear Factor kappa B (NFκB), Activator protein-1 (AP-1) and Signal Transducers and Activators of Transcription (STAT) proteins are some of the well-characterised pro-inflammatory transcription factors. These transcription factors are inducible and regulate the expression of a range of genes involved in important biological processes such as the innate and adaptive immunity, inflammation, cellular stress responses, cell adhesion, apoptosis and proliferation. Regulation of these transcription factors is crucial since dysregulated inflammatory response can lead to acute or chronic inflammatory diseases. Investigations in our laboratory revealed that SNP in a potential immune/inflammation regulatory gene NFKBIL-1 was associated with increased susceptibility to Coeliac Disease in Irish population. In this regard, we characterized the function of a novel protein, thought to be a potential inhibitor of NFκB, Nuclear Factor Kappa B Inhibitor Like-1 protein (NFKBIL-1). We demonstrate that NFKBIL- 1 inhibits IL-1β, TNF-α, TLR2 and TLR4 stimulated NFκB activity. Furthermore, we also report that AP-1 and STATl are also regulated by NFKBIL-1. We did not observe any translocation of NFKBIL-1 out of the nucleus in cells stimulated with various pro- and anti- inflammatory agents, suggesting that it regulates these transcription factors from within the nucleus. Finally, we demonstrate a colocalisation of NFKBIL-1 and HDAC3, providing a potential mechanism by which NFKBIL-I may exert its broad based anti-inflammatory effects.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin